Стандартизація роз’ємів зарядки електромобілів - Борозняк, Д. С. (ХНУРЕ, 2024)
Electric vehicle (EV) charging connectors are standardized and continue to change. On the one hand, connectors for charging electric vehicles are standardized based on the limitations of modern technologies, there are standards in the main regional markets. But current charging technologies have limited capacity, prompting a request to change the status of connector standardization for electric vehicle chargers, and liquid-cooled connectors are being considered for higher-capacity, faster-charging technologies.
Keywords: зарядка електромобілів; стандартизація роз’ємів зарядки електромобілів